Laparoscopic orchidopexy with transabdominal preperitoneal hernia repair in an adult. Issue 3 (24th February 2017) - Omoto, Kenichiro; Nishihara, Yuichi; Kawaguchi, Yoshiki; Urakami, Hidejiro; Seki, Shiko; Ohishi, Takashi; Isobe, Yoh; Matsumoto, Sumio
Abstract: We report an adult who underwent laparoscopic orchidopexy and transabdominal preperitoneal hernia repair. The patient was a 53‐year‐old man who was referred to our hospital for a bulge and pain in his left inguinal area. An abdominal CT scan revealed that the greater omentum was incarcerated in a left inguinal hernia. The patient underwent emergency laparoscopic surgery immediately. After reduction, he was diagnosed with bilateral cryptorchidism and inguinal hernia. After adequate mobilization, pneumoperitoneum was discontinued, and orchidopexy was performed with the Lichtenstein tension‐free hernioplasty. One month later, the patient underwent elective laparoscopic orchidopexy with transabdominal preperitoneal hernia repair on his right side. The patient's postoperative course has been uneventful, with no evidence of hernia recurrence to date. This procedure is safe and may be an option for adult patients who desire testis preservation. This may be the first report of laparoscopic hernia repair with orchidopexy.